Guide to fashion career planning job search, resumes, and strategies for success - Paulins, V. Ann; Hillery, Julie L. (Fairchild Books, 2016)
"Helps both students and individuals interested in entering the fashion industry prepare fur successful careers-- from self-assessment and goal setting to landing the first job. The book presents a seamless and comprehensive approach to everything needed for professional and career development." --back cover.